Policy responses by different agents/stakeholders in a transition: Integrating the Multi-level Perspective and behavioral economics - Ardjan Gazheli; Miklós Antal; Ben Drake; Tim Jackson; Sigrid Stagl; Jeroen van den Bergh; Manuel Scholz-Wäckerle (WWWforEurope, 2013)
This short paper considers all possible stakeholders in different stages of a sustainability transition and matches their behavioral features and diversity to policies. This will involve an assessment of potential or expected responses of stakeholders to a range of policy instruments. Following the Multi-Level Perspective framework to conceptualize sustainability transitions, we classify the various transition policies at niche, regime and landscape levels. Next, we offer a complementary classification of policies based on a distinction between social preferences and bounded rationality. The paper identifies many barriers to making a sustainability transition and how to respond to them. In addition, lessons are drawn from the case of Denmark. The detailed framework and associated literature for the analysis was discussed in Milestone 31 of the WWWforEurope project (Gazheli et al., 2012).
Keywords: D1; D2; D7; D8; E6; H2; L2; L5; O2; Q5; 330; Behavioural economics; beyond GDP; ecological innovation; economic strategy; entrepreneurship; European economic policy; European governance; good governance; industrial innovation; industrial policy; innovation; innovation policy; multi-level governance; policy options; political economy of policy reform; social innovation; socio-ecological transition